A Revenge In Olivier Megaton's Colombiana Movie (2011):A Psychoanalytic Approach - Yuliastuti, Dewi; , Drs. Abdillah Nugroho, M.Hum; , Nur Hidayat, S. Pd (2013)
This research investigates how the revenge influences the major character's personality development in Olivier Megaton, viewed for an individual psychological approach, especially behaviorist perspective. Therefore, the study analyzes the movie in terms of its structural elements based on the individual psychological perspective. This study belongs to qualitative study. In this method, the writer uses two data sources; they are primary and secondary data sources. The primary data source and the object of the study is the movie, Colombiana itself. Meanwhile the secondary one is any books of literature and psychology related to this study. The writer collects the data from both primary and secondary data sources in a sort of document evidence. The result of the data shows the following conclusion: first, the dominant influence building Restrepo's personality is his family, especially her daughter. Her personality is like her father. Second, Cataleya becomes a quiet girl when she was young. This is all because of love, love from her parent. In this movie, Cataleya change to be strong, smart and killer person because of his family's influence.